Pyrroline-5-Carboxylate Reductase in Chlorella autotrophica and Chlorella saccharophila in Relation to Osmoregulation - Laliberté, Gilles (1989)
Pyrroline-5-carboxylate (P5C) reductase (EC 1.5.1.2), which catalyzes the reduction of P5C to proline, was partially purified from two Chlorella species; Chlorella autotrophica, a euryhaline marine alga that responds to increases in salinity by accumulating proline and ions, and Chlorella saccharophila, which does not accumulate proline for osmoregulation. From the elution profile of this enzyme from an anion exchange column in Tris-HCl buffer (pH 7.6), containing sorbitol and glycine betaine, it was shown that P5C reductase from C. autotrophica was a neutral protein whereas the enzyme from C. saccharophila was negatively charged. The kinetic mechanisms of the reductase was characteristic of a ping-pong mechanism with double competitive substrate inhibition. Both enzymes showed high specificity for NADH as cofactor. The affinities of the reductases for their substrates did not change when the cells were grown at different salinities. In both algae, the apparent K(m) values of the reductase for P5C and NADH were 0.17 and 0.10 millimolar, respectively. A fourfold increase in maximal velocity of the reductase was observed when C. autotrophica was transferred from 50 to 150% artificial sea water. Even though the reductase was inhibited by NaCl, KCl, and proline, it still showed appreciable activity in the presence of these compounds at molar concentrations. A possible role for the regulation of proline synthesis at the step catalyzed by P5C reductase is discussed in relation to the specificity of P5C reductase for NADH and its responses to salt treatments.